2021
DOI: 10.1186/s12864-021-07540-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of a Spiroplasma associated with the carmine cochineals Dactylopius coccus and Dactylopius opuntiae

Abstract: Background Spiroplasma is a widely distributed endosymbiont of insects, arthropods, and plants. In insects, Spiroplasma colonizes the gut, hemolymph, and reproductive organs of the host. Previous metagenomic surveys of the domesticated carmine cochineal Dactylopius coccus and the wild cochineal D. opuntiae reported sequences of Spiroplasma associated with these insects. However, there is no analysis of the genomic capabilities and the interaction of this Spiroplasma with Dactylopius. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 105 publications
2
8
0
Order By: Relevance
“…The s Dis symbiont encodes complete ATP synthase and glycolysis pathways, as well as transport components for glucose, fructose, GlcNAc, glycerol, and possibly mannose ( Figure 5 ). Amino acid and lipid biosynthesis pathways are incomplete or absent, as reported previously for hemolymph-dwelling Spiroplasma species, including those in the Ixodetis clade ( Martin et al., 2020 ; Vera-Ponce León et al., 2021 ; Yeoman et al., 2019 ). Incomplete pathway components were identified for lysine ( dapE ), valine, leucine, and isoleucine ( ilvA ), and arginine ( OTC ) synthesis.…”
Section: Resultssupporting
confidence: 70%
“…The s Dis symbiont encodes complete ATP synthase and glycolysis pathways, as well as transport components for glucose, fructose, GlcNAc, glycerol, and possibly mannose ( Figure 5 ). Amino acid and lipid biosynthesis pathways are incomplete or absent, as reported previously for hemolymph-dwelling Spiroplasma species, including those in the Ixodetis clade ( Martin et al., 2020 ; Vera-Ponce León et al., 2021 ; Yeoman et al., 2019 ). Incomplete pathway components were identified for lysine ( dapE ), valine, leucine, and isoleucine ( ilvA ), and arginine ( OTC ) synthesis.…”
Section: Resultssupporting
confidence: 70%
“…The present study confirmed that H. magnanima was infected with the MK S. ixodetis strain s Hm that harbored two distinct 16S rRNA gene sequences in its genome ( Figure 2 ). Moreover, Spiroplasma strains often encode multiple ribosomal RNA gene sets in their genome ( Chang et al, 2014 ; Tsai et al, 2018 ; Vera-Ponce León et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“… 2 Based on Martin et al (2020) . 3 Based on Vera-Ponce León et al (2021) . 4 Based on Pollmann et al (2022) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations